The fight of his life : inside Joe Biden's White House - Whipple, Chris (Scribner, 2023)
Taking readers behind the scenes of one of America's most consequential presidencies, a journalist with unprecedented access to the White House reveals how President Joe Biden and his seasoned team have battled to achieve their agenda, delivering a surprising portrait of politics on the edge.